High Resolution Time-lapse Resistivity Tomography with Merging Data Levels by Two Different Optimized Resistivity Arrays for Slope Monitoring Study - Bery, Andy Anderson; Saad, Rosli; Kiu, Y. C.; Kamaruddin, Nur Aminuda (Mete Oner, 2014)
In this paper, we present high resolution time-lapse resistivity tomography study for slope monitoring using two optimized resistivity arrays of Wenner-Schlumberger and pole-dipole. These optimized resistivity arrays of Wenner-Schlumberger and pole-dipole give total of 2038 datum points for each data set. This slope monitoring study was conducted at Minden, Penang Island, Malaysia. Inversion results from computer suggested that optimized Wenner-Schlumberger and pole-dipole arrays would be equally effective but the merge data levels technique for both arrays would able to provide high resolution at imaging slope area. Our in-field data results showed that the two arrays imaged the subsurface for slope monitoring equally well. When in-field data levels from these two different arrays were merged and analyzed using 2-D inversion, however, the merging data levels using two different arrays was able to resolve the subsurface characterizations. Because the merging data levels using two different arrays requires roughly two times as measurement per line, we conclude that this technique is preferable for environmental geophysics than single array only when the high improvement in resolution at sensitivity, horizontal coverage, signal strength and investigation depth is more important than rapid data acquisition. The overall results using these two different arrays were quite compromising and remarkably significant for good improvement in data quality and data acquisition technique.